II. Documenta '59 : Druckgrafik : Kunst nach 1945 internationale Ausstellung. - Internationale Ausstellung, Kassel (Köln : M. Du Mont Schauberg, 1959)
Adam, Henri - Georges ; Altenbourg, Gerhard ; Appel, Karel ; Arp, Hans ; Baumeister, Willi ; Batz, Eugen ; Beaudin, André ; Beckman, Max ; Bellmer, Hans ; Berke, Hubert ; Bill, Max ; Braque, Georges et al.
II. documenta '59, M. Du Mont Schauberg, Köln, 11.Juli - 11.Oktober 1959
kunstcatalogus